(untitled) (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
This study examines how Social Darwinism shaped Western legal systems in the period between the First and Second World Wars. The application of Darwinian natural selection to social life—particularly through the rise of the eugenics movement—provided a purportedly “scientific” basis for legal interventions grounded in racial hierarchy, public health, and social classification. In this context, Social Darwinism informed mental health, family, and citizenship laws in the United Kingdom; immigration quotas, anti-miscegenation statutes, and compulsory sterilization policies in the United States; and radical racial legislation during the Nazi era in Germany. Similar sterilization programs emerged in several other countries, including Sweden, Norway, Finland, Canada, and Japan. In early Republican Turkey, Social Darwinist debates influenced academic and intellectual discussions, though they did not translate into extensive biopolitical legal practices comparable to those in Western states. Overall, the study argues that Social Darwinism legitimized racist and exclusionary legal measures under the guise of scientific objectivity, and that understanding this legacy is crucial for interpreting the post–World War II development of human rights norms.